Morphological identification of Culicoides spp described as Orbivirus transmitters trapped in sheep farms in Pucallpa, Peru - Navarro M., Dennis (2018)
The aim of the present study was to identify ceratopogonids of the genus Culicoides (Latreille, 1809) involved in the transmission of Orbivirus. The catches were made in two farms located close to Santa Rosa de Lima village, Ucayali, Peru, an area characterized by the presence of shrubs, trees, and wetlands, as well as the breeding of hair sheep, horses and poultry. During three consecutive nights, 7930 specimens of Culicoides spp were captured through five CDC ultraviolet light traps installed next to the flocks. The identification of the Culicoides was done with the support of atlases of photographs of the wing of Neotropical Culicoides and taxonomic keys for each species. Five species were registered within the subgenus Hoffmania (Guttatus and Hylas groups) and another without subgenus classification (Fluvialis group). It was identified 7839 (98.8%) female Culicoides and 91 (1.2%) males. According to relative abundance, the main species was C. insignis (94.8%), followed by C. foxi (3.2%) and C. ocumarensis (1.3%). Other species such as C. pseudodiabolicus, C. hylas and C. leopoldoi were present in densities lower than 0.5%. Also, it was observed a Culicoides sp (n=31) that is in the process of identification.